Methane Reduction Potential of Two Pacific Coast Macroalgae During in vitro Ruminant Fermentation - Brooke, Charles G.; Roque, Breanna M.; Shaw, Claire; Najafi, Negeen; Gonzalez, Maria; Pfefferlen, Abigail; De Anda, Vannesa; Ginsburg, David W.; Harden, Maddelyn C.; Nuzhdin, Sergey V.; Salwen, Joan King; Kebreab, Ermias; et al. (Frontiers in Marine Science, 2020)
With increasing interest in feed-based methane mitigation strategies and regional legal directives aimed at methane production from the agricultural sector, identifying local sources of biological feed additives will be critical for rendering these strategies affordable. In a recent study, the red alga Asparagopsis taxiformis harvested offshore Australia was identified as highly effective for reducing methane production from enteric fermentation. Due to potential difference in methane-reduction potential and the financial burden associated with transporting the harvested seaweed over long distances, we examined locally sourced red seaweed A. taxiformis and brown seaweed Zonaria farlowii for their ability to mitigate methane production when added to feed widely used in the Californian dairy industry. At a dose rate of 5% dry matter (DM), California-sourced A. taxiformis and Z. farlowii reduced methane production by up to 74% (p ≤ 0.05) and 11% (p ≤ 0.05) during in vitro rumen fermentation respectively. No effect on CO2 production was observed for either seaweed. The measured decrease in methane production induced by A. taxiformis and Z. farlowii amendment, suggest that these local macroalgae are indeed promising candidates for biotic methane mitigation strategies in California, the largest milk producing state in the US. To determine their real potential as methane mitigating feed supplements in the dairy industry, their effect in vivo will need to be investigated.